Reprint of Long-term survival and late toxicities of elderly nasopharyngeal carcinoma (NPC) patients treated by high-total- and fractionated-dose simultaneous modulated accelerated radiotherapy with or without chemotherapy. (March 2019) - Miao, Jingjing; Wang, Lin; Zhu, Manyi; Xiao, Weiwei; Wu, Haijun; Di, Muping; Huang, Yuqing; Huang, Shaomin; Han, Fei; Deng, Xiaowu; Guo, Xiang; Zhao, Chong
Highlights: High-dose IMRT greatly improved local control and outcomes in elderly NPC patients. No grade 4 toxicities were observed, except for acute haematologic toxicities. CCRT did not seem to improve long-term survival of stage II–IVb elderly NPC patients. Abstract: Background: To analyse the survival and late toxicities of elderly nasopharyngeal carcinoma (NPC) patients treated by intensity-modulated radiotherapy (IMRT) with the high-total- and fractionated-dose simultaneous modulated accelerated radiation therapy (SMART) boost technique and to identify the effect of concurrent chemotherapy for these patients. Methods: Two hundred and fifty-four elderly patients (age ≥ 60.0) with newly diagnosed non-metastatic NPC were retrospectively analysed. Statistical analyses were performed using the SPSS software program. Results: The actual mean total and fractionated doses delivered to the gross tumour volume of the nasopharynx (GTVnx) were 74.55 Gy and 2.49 Gy, respectively. The 5-year locoregional recurrence-free survival (LRRFS), distant metastasis-free survival (DMFS), disease-specific survival (DSS) and overall survival (OS) of the whole cohort were 93.0%, 85.7%, 83.2% and 74.1%, respectively. No grade 4 acute or late radiotherapy-induced toxicities were observed. Of 247 patients with stage II–IVb disease, 89 patients received radiotherapy (RT) alone, and 158 patients received concurrent chemoradiotherapy (CCRT), and the 5-year LRRFS, DMFS, DSS and OS of the RT-alone group vs. the CCRT group were 94.0% vs. 92.2%, 83.5% vs. 86.2%, 81.8% vs. 83.1% and 74.0% vs. 72.8% (all P > 0.05), respectively. Multivariate analyses showed that CCRT was not an independent predictor for LRRFS, DMFS, DSS and OS (all P > 0.05). Conclusion: High-total- and fractionated-dose SMART boost IMRT could obtain a satisfactory long-term outcome with mild late toxicity in elderly NPC patients. The role of CCRT needs to be further studied to optimize the treatment strategy and improve the overall survival.